KONSISTENSI PEMERINTAH DAERAH KOTA PEKANBARU DALAM MENJAGA KETERTIBAN UMUM (STUDI KASUS PEDAGANG KAKI LIMA) - Fitria, Nurul; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Consistency is one of the important key in the process of policyimplementation due to the successful achievement of specified goals withcontinuous action. The problem of street vendors into a phenomenon that is stilldifficult to overcome. In this case the Civil Service Police Unit of Pekanbaruresponsible for regulating street vendors. Lack of resources and supportinginfrastructure of labor, lack of existing regulations and lack of adherence to thelaw society will be a major obstacle in efforts Pekanbaru City municipal police inrunning public order. Basically consistency can be measured by indicators of thestability program, compliance with the program of action has been set, andcommitment. If these indicators are met, then with a good level of consistency thatcan achieve the goals that have been set.The purpose of this study was to determine the consistency of PekanbaruCity Government in maintaining public order, case studies Street Vendors inPekanbaru and also to determine the factors that influence the consistency memPekanbaru City Government in maintaining order umu, especially street vendors.In this study the authors using Snowball Sampling. Data collection techniques inthis study namely through observation, interviews, and documents. Indicators inthis study that affect the consistency of Pekanbaru City Government inmaintaining public order, the case study of street vendors is a personal number,SOP, unfamiliarity will rule society.Results of this study concluded that the Civil Service Police Unit ofPekanbaru has not been consistent in maintaining order five street vendors in thecity of Pekanbaru. This is due to lack of resources, facilities and infrastructurework and public awareness of the regulations that affect the consistency inimplementing the rules that have been set. Through this study the authorsconclude that the Civil Service Police Unit of Pekanbaru has not been consistentin maintaining order five street vendors in the city of Pekanbaru. Therefore, theadvice given in the last part of the research is to improve the consistency ofPekanbaru City Government in maintaining public order, especially streetvendors.Keywords : Consistency, Model Policy Implementation, Public Order, StreetVendors